Strategi Pengembangan dan Analisis Kelayakan Usaha Pertanian Padi Organik Bersertifikat SNI Pangan Organik (Studi Kasus Pada Operator Organik di Jawa Timur) - Samudi . (Universitas Islam Kadiri, 2016)
Strategy is fine of using profeciency and resources to get targets in correlative relation with the most profitable environment condition. Strategy is also clarified a continuing response in adaptivable to chance and threatment or extern challenging, internal strenght and weakness which can influence goal achievement of organic rice agriculture. That statement can be concluded that strategy is the orientation or the rule of how to make long term natural resouces and get up to the purpose in certain time by looking the internal and external natural factor ( Nadarfuddin, 2009 ). Strategy is designed and practiced to get the goal of organization not only short term but also long term. So, strategy deciphers means to ends. Ends is a wished condition in the future. Gibson ( 1993 ) clarified about three time of effectivity organization. They are : a. Short term effectivity : production, efficiency, and satisfaction; b. middle term affectivity : addaptiveness and development; c. Long term activity : survival. Organic agriculture in International Federation of Organic Agriculture Movements (IFOAM) is holistic and cohesive agriculture production system by optimizing quality and agro-ecosystem naturally, so it produces good food, quality and continuing. Organic agriculture is a holistic agricultural sytem which supports and quickens biodeversity, biology scycle, and biology soil. Expendience of finance analysis is a cost analysis as for or fit to get advantages from the business ( Sunarto 2002 ). Furthermore, Gittinger ( 1986) said that financial influence from a project to partipants there ( farmers ). The tittle of Strategy and Expendient of Agribusiness is taken based on some statement of problems 1. How the Developmental StrategyOrganic Rice in East Java is and 2. How Expendient finance of agribusiness organic rice in East Java is. The research pupose is to apply Developmental Strategy Organic Rice in East Java and to know the expendient agribusiness of organic rice in East Java. The result of research is Developmental Strategy and Expendient Agribusiness Organic Rice, cerificated SNI of organic food, got from strategic assumption selection such as :1. Create the farmer organization; 2. Keep and warrant agriculture product based on SNI and Food International; 3. Increase human resources and natural resources of organic agriculture based on SNI and free trade; 4. Use local natural resouces to staunch the organic quality product5. Increase regional, regional billateraly and international business partners; 6. Maximize the guidance and supervisor to stay of organic quality product; 7. Develop distribution link of organic product integrity. On other hand, the analysis results of Expendient of Agribusiness are : the result of Expendient Agribusiness Organic Rice in 1 ha land (1) the farmer income is 10.935.760 rupiah in acultivating season; 2. Analysis result RC ratio > 1 is 1,57. It means that in every additional cost 100 rupiah will accept 157 rupiah which shows that organic rice profits in a period ( one cultivating season ); 3. The period of investation returning is for 2,5 months. It shows that invested fund will be accepted 19.064.240 rupiah when the business has been doing for 2,5 months. The break event point production is 2.545 kilograms when the farmers are not being fault and being luck and the break event point cost is 3.177,37 rupiah. But the receiption is 10.797.754 rupiah.